Crude Oil Pipeline Scale Deposition: Causes and Removal Methods (University of Khartoum Engineering Journal, 2022)
This work investigated the causes of scale formation and removal methods on 107 km crude oil pipelineof Diffra oil field of Muglad basin as a case study. The study is based on well and pipeline historical data of threeyears (2007, 2008 and 2009). The data included production data (net oil and water cut), choke opening, pipelinepressures, water qualities and scale composition. The study revealed that the main cause of scale formation is thepresence of Ca+2 and Mg+2 in produced water and wax in oil. The scale consists of 78 % Ca+2, 12 % Mg+2 and10 % wax. Investigations on removal methods revealed that the currently employed chemical removal method iseffective; however the downtime (well shut down) is high making significant production cut. A method to reducethe cleaning down time is proposed. The pipeline is divided into two sections: aboveground and underground. Theaboveground line is characterized with the presence of valves, choke and pipe reductions (i.e. non uniform crosssection). The underground section is uniform in cross sectional area. For the aboveground section the currentpractice of chemical cleaning is recommended to be maintained however, with provision of a bypass line. Forunderground section the standard practice of pigging is recommended. The proposed cleaning method of the wholepipeline eliminates the downtime completely. In addition it is uncomplicated, with economical operation andinstallation cost. The method also make significant cut in chemical used hence reduces the hazard andenvironmental impacts.